ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI TEH SEDAP WANGI MENGGUNAKAN METODE HARGA POKOK PROSES PADA PT. SARIWANGI A.E.A - Afif, Muhammad Nur; Rahmawati, Dera Rahayu (Jurnal Akunida, 2018)
This research aims to determine production cost of Sedap Wangi tea using by cost method at PT. Sariwangi A.E.A. TheCalculation of cost production using by cost method process is collected in a production department. Cost method process used weighted average method. Methods and tools of the data collection by interview and collection of data obtained directly from the company, and the result of this research calculation the cost production by using cost method process Produce cost of production is same with the calculation by the company, so it can be said that the calculation of cost production at PT. Sariwangi A.E.A complies done. Calculation of the cost production is influenced by the product is lost in the process and load of cost. Cost of the highest production at PT. Sariwangi A.E.A contained in quartile 4 the period October-Decemberbecause in that period decreased production yield and many products lost in the process. Cost of production in the quartile 4 of Rp 54.742. Lowest Cost of production happen in quartile 2 period April-june, because the result of increased production in the period and not a lot of product is lost in the process. Cost of production in the quartile 2 of Rp 48.004. Key words : Cost of Production, Cost of Process Method